Detection of Merkel Cell Polyomavirus DNA in Serum Samples of Healthy Blood Donors - Mazzoni, Elisa; Rotondo, John C.; Marracino, Luisa; Selvatici, Rita; Bononi, Ilaria; Torreggiani, Elena; Touzé, Antoine; Martini, Fernanda; Tognon, Mauro G. (Frontiers in Oncology, 2017)
Merkel cell polyomavirus (MCPyV) has been detected in 80% of Merkel cell carcinomas (MCC). In the host, the MCPyV reservoir remains elusive. MCPyV DNA sequences were revealed in blood donor buffy coats. In this study, MCPyV DNA sequences were investigated in the sera (n=190) of healthy blood donors. Two MCPyV DNA sequences, coding for the viral oncoprotein large T antigen (LT), were investigated using PCR methods and DNA sequencing. Circulating MCPyV sequences were detected in sera with a prevalence of 2.6% (5/190), at low DNA viral load, which is in the range of 1-4 copy/µl and 1-5 copy/µl by RT-PCR and ddPCR, respectively. DNA sequencing carried out in the 5 MCPyV-positive samples indicated that the two MCPyV LT sequences which were analysed belong to the MKL-1 strain. Circulating MCPyV LT sequences are present in blood donor sera. MCPyV-positive samples from blood donors could represent a potential vehicle for MCPyV infection in receivers, whereas an increase in viral load may occur with multiple blood transfusions. In certain patient conditions, such as immune-depression/suppression, additional disease or old age, transfusion of MCPyV-positive samples could be an additional risk factor for MCC onset.